In the field : from learning to practice - 4 0 16; Giles, Roslyn.;Irwin, Jude.;Lynch, Denise.;Waugh, Fran.; 5 (Australia : Oxford University Press, 2010)
Professional education through the practicum process enables human service students to apply their skills and prepare themselves for making the transition to practice. This book, with its focus on life- long learning, helps students to enhance those essential skills. Authors from University of Sydney.
Includes bibliographical references (p. 230-239) and index.
Keywords: 2 -- 0; 6; Training of.;Training of.;Education. -- Medical education.;Medical personnel;Health care teams;Public health personnel; 20; 2